Studi Literatur: Pemanfaatan Model Radec Terhadap Keterampilan Berpikir Tingkat Tinggi dalam Pembelajaran PKN di Sekolah Dasar - Hernita Hernita; Surya Dharma (Journal on Education, 2023)
For The purpose of the research to describe the RADEC learning model that is used as a tool in cultivating students' high-order thinking skills in Civics learning in elementary schools. The data were collected through a literature review from several sources, namely indexed journals and scientific articles. The sources obtained must be related to the problems to be discussed in the research. Data analysis was carried out by reducing data that had been collected and then described scientifically so that conclusions could be drawn. This research resulted in Civics learning solutions that can foster higher-order thinking skills, namely the use of a model with Read-Answer-Discuss-Explain-And Create (RADEC) stages.